Development of Online Needs-Based Workshop Support System in a Pandemic - Murata, Hidenori; Horio, Seisuke; Kobayashi, Hideki (Frontiers in Sustainability, 2021)
The sustainable development goals, adopted in 2015, include achievement of sustainable consumption and production (SCP) patterns as the 12th goal. To achieve SCP patterns, it is necessary not only to reduce environmental load caused by production and manufacturing but also to improve the sufficiency of fundamental human needs and the quality of life of consumers. The living-sphere approach aims to design products for a target living sphere by determining the sufficiency of fundamental human needs among local residents through products using the fundamental human needs framework proposed by Max-Neef. This framework consists of fundamental human needs and satisfiers. Max-Neef argued that fundamental human needs are universal, but satisfiers fulfilling these fundamental human needs depend on region, culture and time. The satisfiers have previously been extracted by needs-based participatory workshops, but during the ongoing coronavirus disease 2019 (COVID-19) pandemic, these in-person workshops can no longer be held. In this study, we developed an online needs-based workshop (NBW) support system to replace the in-person NBW. The developed system consists of digital applications such as an online whiteboard service, video meeting service and original software to support facilitation. We applied the developed system to online NBWs held in Japan to verify the developed system and to validate whether the online NBW can replace the in-person NBW. The results verified that the developed system was working as designed. Comparison of the results between online and in-person sessions validated that replacing the in-person NBW with an online NBW using the developed system was highly possible.